Microstructural integrity of autonomic central nervous tracts is linked to cardiovascular health - Janis M. Nolde; Alexander Rau; Elias Kellner; Horst Urbach; Cornelius Weiller; Fabian Bamberg; Jakob Weiss; Marco Reisert; Jonas A. Hosp (Neurobiology of Disease)
Introduction: The central autonomic network (CAN), which controls sympathetic and parasympathetic activity, plays a central role in the pathogenesis of cardiovascular disease and serves as a target for therapeutic approaches. This study investigates the association of microstructural integrity of white matter fibres representing the CAN with cardiovascular damage, risk and outcomes using a large population-based cohort study. Methods: The microstructural integrity of the CAN was evaluated using magnetic resonance imaging (MRI) of the brain from the population-based UK Biobank study applying previously developed diffusion imaging data-processing techniques. Subsequently, measures of cardiac and vascular organ damage (i.e. left ventricular (LV) myocardial mass, LV wall myocardial thickness and arterial stiffness index) were correlated with the integrity of CAN fibres and other brain regions. Furthermore, the patterns of regional CAN associations with cardiovascular organ damage and major adverse cardiovascular events (MACE) following imaging were analysed. Both cortical and subcortical components of the CAN were examined separately. Results: A total of 43,994 individuals were included in the analysis (mean age: 55.0 ± 7.5 years, 53 % females). The microstructural integrity of the CAN demonstrated stronger associations with cardiac and vascular organ damage parameters than with brain regions outside the CAN. In cortical CAN tracts, measures of cardiac and vascular damage were positively associated with the free water compartment, whereas a negative association existed for intra-axonal volume (all p < 0.001). Also, the proportion of free water in CAN fibres interconnecting the cingulum and the insular cortex was a strong predictor of MACE. A 10 % increase in the free-water compartment of these brain tracts was associated with a hazard ratio for MACE after imaging of 3.8 (95 % CI: 2.1–6.9; p < 0.001) and 4.2 (95 % CI: 2,1–8.4; p < 0.001), for left and right side respectively). Subcortical CAN components showed modest associations, particularly between increased intra-axonal volume and cardiac parameters. Conclusion: Our findings indicate a distinct association between the integrity of brain networks regulating autonomic activity and cardiovascular health. Particularly, connections between the rostral-anterior cingulum and the insular cortex may be associated with higher risk for future MACE. Differential patterns were observed in cortical versus subcortical CAN structures, suggesting distinct pathophysiological roles within the heart-brain axis.